Quantifying fatal and non‐fatal drowning in children under five in Aotearoa, New Zealand - Amy E. Peden; Karen Richardson (Elsevier, 2022)
Abstract Objective: To quantify unintentional drowning trends and risk factors for children under five years of age in Aotearoa, New Zealand. Methods: A population‐based analyses of fatal and non‐fatal (hospitalisations and Accident Compensation Corporation [ACC] claims) unintentional drowning of children 0‐4 years of age between 2005 and 2019 was conducted using DrownBase™ data. Analyses comprises calculation of linear temporal trends, crude drowning rates per 100,000 and relative risk (95% confidence interval) and ratios of fatal to non‐fatal drowning. Results: 557 incidents (16.0% fatal) were recorded. Fatalities declined (y=−0.0769x+2.5678;R2=0.01509), while hospitalisations increased (y=0.1418x+9.1093;R2=0.0979). Males were overrepresented. One year‐olds recorded the highest rates (fatal=4.39/100,000) and (non‐fatal=2.14/100,000). 'Other' ethnicity (8.77/100,000) and Māori (2.49/100,000) children recorded the highest fatal drowning rates. Home pools were the leading fatal location, while domestic environments attracted the highest hospitalisation rate. For every one fatal drowning there were 6.9 hospitalisations and 74.7 ACC claims. Conclusions: Drowning among young children represents a preventable cause of injury‐related harm. While fatalities are declining, non‐fatal drowning is increasing. Implications for public health: Strategies to prevent drowning among young children are well understood, particularly restricting water access and active adult supervision. Further investment in effective prevention strategies for young children will deliver significant social, economic and health system savings.